A cyclic lipopeptide produced by an antagonistic bacterium relies on its tail and transient receptor potential‐type Ca2+ channels to immobilize a green alga. Issue 5 (28th December 2022) - Hou, Yu; Bando, Yuko; Carrasco Flores, David; Hotter, Vivien; Das, Ritam; Schiweck, Bastian; Melzer, Tommy; Arndt, Hans‐Dieter; Mittag, Maria
Summary: The antagonistic bacterium Pseudomonas protegens secretes the cyclic lipopeptide (CLiP) orfamide A, which triggers a Ca 2+ signal causing rapid deflagellation of the microalga Chlamydomonas reinhardtii . We performed chemical synthesis of orfamide A derivatives and used an aequorin reporter line to measure their Ca 2+ responses. Immobilization of algae was studied using a modulator and mutants of transient receptor potential (TRP)‐type channels. By investigating targeted synthetic orfamide A derivatives, we found that N ‐terminal amino acids of the linear part and the terminal fatty acid region are important for the specificity of the Ca 2+ ‐signal causing deflagellation. Molecular editing indicates that at least two distinct Ca 2+ ‐signaling pathways are triggered. One is involved in deflagellation (Thr 3 change, fatty acid tail shortened by 4C), whereas the other still causes an increase in cytosolic Ca 2+ in the algal cells, but does not cause substantial deflagellation (Leu 1 change, fatty acid hydroxylation, fatty acid changes by 2C). Using mutants, we define four TRP‐type channels that are involved in orfamide A signaling; only one (ADF1) responds additionally to low pH. These results suggest that the linear part of the CLiP plays one major role in Ca 2+ signaling, and that orfamide A uses a network of algal TRP‐type channels for deflagellation.